Integrated assurance : risk governance beyond boundaries - Kubitscheck, Vicky (Gower Publishing Limited, 2014)
Much has been written about assurance, but mainly by those who provide it - the professionals such as internal auditors, accountants and information security technologists for the purpose of advancing their professional practices. Less is written for or by those in governance who need it for the effective discharge of their responsibilities. It is time to rethink assurance beyond its usual functional boundaries, to focus on what matters to the business and how discussions in the board room can be better supported by more joined up assurance. This book will provide practical guidance for those.